Perbedaan Kadar Leukosit dan Limfosit Paska Pemberian Kombinasi Vitamin B Parenteral Pada Pasien Penyakit Ginjal Kronik dengan Hemodialisis - Rizaldy Taslim Pinzon; Ester Novitasari; Nining Sri Wuryaningsih (Universitas Wijaya Kusuma Surabaya, 2021)
Chronic kidney disease is a disease in which kidney function decreases progressively irreversibly with various etiologies. Patients with chronic kidney disease are generally immunosuppressed and susceptible to infection. Some of the causes are abnormalities in polymorphonuclear leukocytes and lymphocytes. The results of several studies indicate that patients undergoing hemodialysis have low levels of water-soluble vitamins. A decrease in the number of leukocytes can also occur due to a decrease in neutrophils and lymphocytes which may be caused by deficiency of vitamins B6 and B12 due to hemodialysis. This study aims to measure the difference in levels of leukocytes and lymphocytes after parenteral vitamin B combination administration in patients with chronic kidney disease undergoing hemodialysis This research is a quasi-experimental design, One Group Pretest Posttest, on 115 selected patients. Patients were given vitamin B1 ,B6 ,B12 parenterally every time doing hemodialysis, twice a week given for 1 month during hemodialysis. The data were taken in the form of leukocyte count, patient lymphocyte percentage, and absolute lymphocyte concentration. The intervention of vitamins B1, B6, B12 was given parenterally to the patient. After collect the data, the leukocyte counts, lymphocyte percentage and absolute lymphocyte concentration before and after the intervention were seen, then it was seen how the effect of parenteral administration of vitamins B1 ,B6 ,B12 on the leukocyte count, lymphocyte percentage and absolute lymphocyte concentration in patients undergoing hemodialysis. From the results of the study, there were 115 patients consisted of 72 men (62.6%) and 43 women (37.4%). There was a difference and effect of giving combination vitamin B in the form of a significant change in the mean number of leukocytes at visits 1-2 with p-value = 0.033. There was a change in the mean of lymphocyte percentage and absolute lymphocyte concentration after administering vitamins B1, B6 ,B12 , but the changes were not significant.